Correlation of neck-shaft angle with functional recovery following internal fixation of intertrochanteric femur fractures: a prospective observational study - Biradar, Siddanagouda B.; Joshi, Gururaj R. (International Journal of Research in Orthopaedics, 2025)
Background: Intertrochanteric femur fractures are a common orthopaedic injury among the elderly. The postoperative neck-shaft angle (neck-shaft angle (NSA)) is a critical biomechanical parameter that may influence functional outcomes following internal fixation. This study aimed to assess the correlation between NSA and functional recovery in patients treated with proximal femoral nail (proximal femoral nail (PFN)) or proximal femoral nail (PFN)A2. Methods: This prospective observational study included 80 patients aged >45 years with intertrochanteric femur fractures treated using PFN or proximal femoral nail anti-rotation 2 (PFNA2). NSA, femoral neck shortening and Harris Hip Score (Harris Hip Score (HHS)) were evaluated at immediate postoperative, 3 months and 6 months intervals. Statistical analysis included Pearson correlation, multivariate regression and ANOVA. Results: At 6 months, NSA positively correlated with HHS (r=0.296, p=0.0077). Patients with NSA between 125°-135° showed statistically significantly better outcomes (63% excellent/good), while those with varus alignment (<125°) had poor outcomes in 83% of cases. Age negatively correlated with recovery (r=-0.452, p<0.0001). Closed reduction and PFNA2 implants were associated with more favourable results. Conclusions: Restoration of NSA within the physiological range (125°-135°) is significantly associated with improved functional outcomes following intertrochanteric fracture fixation. Accurate anatomical alignment should be a surgical priority, particularly in elderly patients.